2008
DOI: 10.1063/1.2945300
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-modified structure of Ge25Sb15S60 and Ge35Sb5S60 glasses

Abstract: Atomic structures of Ge 25 Sb 15 S 60 and Ge 35 Sb 5 S 60 glasses are investigated in the ␥-irradiated and annealed after ␥-irradiation states by means of high-energy synchrotron x-ray diffraction technique. The first sharp diffraction peak ͑FSDP͒ is detected at around 1.1 Å −1 in the structure factors of both alloys studied. The FSDP position is found to be stable for radiation/annealing treatment of the samples, while the FSDP intensity shows some changes between ␥-irradiated and annealed states. The peaks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…Thus, when the radiation-induced structural changes in ChGs occur towards the disordering on the MRO scale and no changes or ordering on the SRO scale, the non-defective mechanism in the frame of the distortion model and any other models (if exist), resulting in a final structural configuration without charged defects, is dominant. On the other hand, the established for Ge-S based glasses the long-term radiation-induced structural changes in DBAL data [2,11,14], when the FSDP remains practically unchanged [2] or its intensity can be something higher [16] and peak is probably something narrower upon γ-irradiation, have been interpreted within the defective CTD model, involving atomic rearrangements directly in the first coordination shells (first-nearest-neighbor atomic correlations), that is, on the SRO scale. The unobservable changes in the FSDP and/or the FSDP sharping and narrowing means that no changes or increasing the MRO structural correlation length and, consequently, a stable MRO structure and/or rise of ordering on the MRO scale take place.…”
Section: Semiconductor Physics Quantum Electronics and Optoelectronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when the radiation-induced structural changes in ChGs occur towards the disordering on the MRO scale and no changes or ordering on the SRO scale, the non-defective mechanism in the frame of the distortion model and any other models (if exist), resulting in a final structural configuration without charged defects, is dominant. On the other hand, the established for Ge-S based glasses the long-term radiation-induced structural changes in DBAL data [2,11,14], when the FSDP remains practically unchanged [2] or its intensity can be something higher [16] and peak is probably something narrower upon γ-irradiation, have been interpreted within the defective CTD model, involving atomic rearrangements directly in the first coordination shells (first-nearest-neighbor atomic correlations), that is, on the SRO scale. The unobservable changes in the FSDP and/or the FSDP sharping and narrowing means that no changes or increasing the MRO structural correlation length and, consequently, a stable MRO structure and/or rise of ordering on the MRO scale take place.…”
Section: Semiconductor Physics Quantum Electronics and Optoelectronicsmentioning
confidence: 99%
“…It has been suggested that the non-defective mechanism within the distortion model for g-As 2 S 3 and the defective mechanism within the coordination topological defects (CTDs) model for g-Ge 15.8 As 21 S 63.2 took place [11,14], since the latter CTD model has been evidently verified using Raman spectroscopy studies, employing the differential representation of depolarized Raman spectra [13]. The CTD approach used for g-Ge 15.8 As 21 S 63.2 or (As 2 S 3 ) 0.4 (GeS 2 ) 0.6 alloy with the dominant Ge-S subsystem seems to be valid for major Ge-S based chalcogenides (see, for example, [15][16][17]). …”
Section: Introductionmentioning
confidence: 99%
“…(a) The total structure factors S(Q) for the samples of the investigated Ge x As 40-x S 60 system in -irradiated (the curves for -irradiated state is shifted (+1) for clarity) and annealed after -irradiation states; and (b) the first sharp diffraction peak (FSDP) in -irradiated and annealed after -irradiation states. difference is notably larger than the total experimental error of the structure factor, which is estimated to be below 1% in the low Q-part of S(Q) as shown in [18]. glasses, both in the -irradiated and annealed after -irradiation states.…”
Section: Resultsmentioning
confidence: 91%
“…A maximum at r = 3.55-3.60 Å reflects the second coordination sphere. Also, a hump at r = 2.99 Å is observed on g(r) of all the investigated samples in the second coordination shell like to the samples of Ge x Sb 40-x S 60 with x = 25 and 35 [18]. But due to the risk that this hump may come from the termination effect, we will not analyze this hump in further consideration.…”
Section: Fig 2 (A) the Pair Distribution Functions G(r)mentioning
confidence: 99%
See 1 more Smart Citation